Cerebrolysin combined with rehabilitation promotes motor recovery in patients with severe motor impairment after stroke. Issue 1 (December 2016) - Chang, Won; Park, Chang-hyun; Kim, Deog; Shin, Yong-Il; Ko, Myoung-Hwan; Lee, Ahee; Jang, Shin; Kim, Yun-Hee
Abstracts Background Cerebrolysin is a neuropeptide preparation with neuroprotective and neurorestorative effects. Combining Cerebrolysin treatment with a standardized rehabilitation program may have a potential synergistic effect in the subacute stage of stroke. This study aims to evaluate whether Cerebrolysin provides additional motor recovery on top of rehabilitation therapy in the subacute stroke patients with moderate to severe motor impairment. Methods This phase IV trial was designed as a prospective, multicenter, randomized, double-blind, placebo-controlled, parallel-group study. A total of 70 patients (Cerebrolysinn = 35, placebon = 35) with moderate to severe motor function impairment were included within 7 days after stroke onset and were randomized to receive a 21-day treatment course of either Cerebrolysin or placebo, given in addition to standardized rehabilitation therapy. Assessments were performed at baseline, immediately after treatment as well as 2 and 3 months after stroke onset. The plasticity of motor system was assessed by diffusion tensor imaging and with resting state functional magnetic resonance imaging. Results Both groups demonstrated significant improvement in motor function (p < 0.05); however, no significant difference was found between the two groups. In the stroke patients with severe motor impairment, the Cerebrolysin group exhibited significantly more improvement in motor function compared with the placebo group (p < 0.05). Effects of Cerebrolysin were demonstrated as restricted increments of corticospinal diffusivity and as recovery of the sensorimotor connectivity. Conclusion The combination of standard rehabilitation therapy with Cerebrolysin treatment in the subacute stroke has shown additional benefit on motor recovery and plastic changes of the corticospinal tract in patients with severe motor impairment. Trial registration NCT01996761 (November 5, 2013)